Point‐Counterpoint: Indirect Calorimetry Is Essential for Optimal Nutrition Therapy in the Intensive Care Unit. (18th March 2021) - Wischmeyer, Paul E.; Molinger, Jeroen; Haines, Krista
Abstract: Iatrogenic malnutrition and underfeeding are ubiquitous in intensive care units (ICUs) worldwide for prolonged periods after ICU admission. A major driver leading to the lack of emphasis on timely ICU nutrition delivery is lack of objective data to guide nutrition care. If we are to ultimately overcome current fundamental challenges to effective ICU nutrition delivery, we must all adopt routine objective, longitudinal measurement of energy targets via indirect calorimetry (IC). Key evidence supporting the routine use of IC in the ICU includes (1) universal societal ICU nutrition guidelines recommending IC to determine energy requirements; (2) data showing predictive equations or body weight calculations that are consistently inaccurate and correlate poorly with measured energy expenditure, ultimately leading to routine overfeeding and underfeeding, which are both associated with poor ICU outcomes; (3) recent development and worldwide availability of a new validated, accurate, easy‐to‐use IC device; and (4) recent data in ICU patients with coronavirus disease 2019 (COVID‐19) showing progressive hypermetabolism throughout ICU stay, emphasizing the inaccuracy of predictive equations and marked day‐to‐day variability in nutrition needs. Thus, given the availability of a new validated IC device, these findings emphasize that routine longitudinal IC measures should be considered the new standard of care for ICU and post‐ICU nutrition delivery. As we would not deliver vasopressors without accurate blood pressure measurements, the ICU community is only likely to embrace an increased focus on the importance of early nutrition delivery when we can consistently provide objective IC measures to ensure personalized nutrition care delivers the right nutrition dose, in the right patient, at the right time to optimize clinical outcomes.